Crack propagation in a brittle DCB specimen assessed by means of the Williams’ power expansion - Lucie Malikova; Seyed Mohammad Javad Razavi; Filippo Berto (Fracture and Structural Integrity)
A double cantilever beam geometry has been chosen in order to investigate the importance of the higher-order terms of the Williams’ power expansion for the crack path estimation. The crack propagation has been tested experimentally on a brittle polymethylmethacrylate (PMMA) specimen and although the mode I loading conditions were applied, the crack kinked from its original plane immediately and propagated towards the bottom side of the specimen. It has been shown that this phenomenon is connected to the magnitude and sign of the T-stress and to the level of the constraint generally. In this work, the influence of the third and higher terms of the Williams’ series on the crack propagation is investigated. The generalized form of the well-known maximum tangential stress fracture criterion for determination of the crack propagation angle has been tested and discussed. The observed differences in the crack trajectory of different specimens have been found to be related to the magnitude of the higher-order terms of the stress tensor components at the crack tip.